Polyurethane scaffold for the treatment of medial meniscus deficiency: clinical and mri outcomes at 48 months follw-up. Issue 3 (23rd March 2016) - Efe, Turgay; Schüttler, Karl; Roessler, Philip; Haberhauer, Felix
Aims and Objectives: The preservation of meniscal structure and function after segmental meniscal loss is of crucial importance to prevent early development of osteoarthritis. Implantation of artificial meniscal implants has been reported as a feasible treatment option. The purpose of this study was to assess the clinical and magnetic resonance imaging (MRI) results 4 years after implantation of a polyurethane scaffold for chronic segmental medial meniscus deficiency following partial medial meniscectomy. Materials and Methods: Twenty patients received arthroscopic implantation of an Actifit® polyurethane meniscal implant (Orteq S Medicine, London, UK) for deficiency of the medial meniscus. Patients were followed at 6, 12, 24 and 48 months. Clinical outcome was assessed using established patient-reported outcome scores (KOOS, KSS, UCLA activity scale, VAS for pain). Radiological outcome was quantified by MRI scans after 6, 12, 24 and 48 months evaluating scaffold morphology, tissue integration and status of the articular cartilage as well as signs of inflammation. Results: Mean patient age was 29.3 years (range 18 to 47 years) with a mean meniscal defect size of 46 mm (range 35 to 62 mm). Continuing improvement of the VAS and KSS Knee and Function Scores could be observed after 48 months compared to baseline, whereas improvement of the activity level according to UCLA continued only up to 24 months and decreased from there on. The KOOS Score showed significant improvement in all dimensions. MRI scans showed reappearance of bone bruises in 2 patients with scaffold extrusion. No significant changes of the articular cartilage could be perceived. Conclusion: Arthroscopic treatment of patients with chronic segmental meniscal loss using the a polyurethane meniscal implant can achieve sustainable mid-term results regarding pain reduction and knee function.